Species diversity of epigeal spider assemblages (Araneae) in coniferous forests in the north of Belarus - Kazulka, Mikalai H.; Zhukovets, Evgeni M.; Semeniak, Alexey A. (Experimental Biology and Biotechnology, 2025)
The article presents materials on the species composition and taxonomic structure of epigeal spider assemblages in coniferous forests on the territory of republican landscape reserves «Osveisky», «Krasny Bor» and «Sinsha» (Vitebsk Region) in the late spring – early summer period. A total of 95 species of spiders were recorded. In the reserve «Osveisky», 38 species were found, in the reserve «Krasny Bor» – 73 species, and in the reserve «Sinsha» – 61 species. In different biotopes, 38–55 species were identified. Depending on the habitat, Trochosa terricola, Tapinocyba pallens, Pocadicnemis pumila, Hygrolycosa rubrofasciata, Alopecosa taeniata, Agroeca brunnea, Walckenaeria cucullata, Xysticus obscurus and Trochosa spinipalpis dominated. Analysis of beta-diversity showed significant differences in the species composition of spiders, which were more similar in the wetter pine forests, as well as in the pine forests of the reserve «Sinsha».
Keywords: spiders; Araneae; species diversity; taxonomic structure; reserve; coniferous forests; Belarus